Rapid detection of Burkholderia glumae, causing panicle blight of rice, by colorimetric Loop-Mediated Isothermal Amplification (LAMP) - Catausan, Sheryl; Grande, Genelou; Schepler-Luu, Van; Castellion Martina (International Rice Research Institute, 2025)
Bacterial panicle blight (BPB), caused by Burkholderia glumae, is an emerging threat to rice production, leading to significant yield losses. The seedborne nature of B. glumae amplifies its threat to seed production, transboundary movement and plant quarantine. Rapid detection and accurate identification are critical in implementing effective containment measures and preventing the spread of the disease. However, existing diagnostic methods such as PCR and culture-based techniques using semi-selective medium are often complex, time consuming, and limited to well-equipped laboratories. This study aims to develop a rapid, cost-effective, and field-deployable detection method using loop-mediated isothermal amplification (LAMP). Unlike conventional PCR methods that require electrophoresis, LAMP results can be easily detected through turbidity, fluorescence, or color changes as in colorimetric LAMP (cLAMP), making it suitable for on-field diagnosis. Using primers designed based on the 16-23S rDNA ITS region of B. glumae, the cLAMP assay described here demonstrates high sensitivity and specificity, differentiating B. glumae strains from other common rice-infecting bacteria; and successfully detects B. glumae in DNA, cell cultures, and crude extracts of infected rice seeds, leaf sheath and panicle, with 105 CFU/ml and 0.1ng to 1pg DNA detection limit. The rapid, simple, and relatively low-cost detection of this method is particularly beneficial to laboratories in developing countries, where resources and equipment for sophisticated diagnostic testing are often limited.